Iron-catalyzed oxidative sp3 carbon–hydrogen bond functionalization of 3, 4-dihydro-1, 4-benzoxazin-2-ones. Issue 91 (19th September 2016) - Huo, Congde; Dong, Jie; Su, Yingpeng; Tang, Jing; Chen, Fengjuan
Abstract : Iron-catalyzed sp 3 C–H bond functionalization of benzoxazinones has been developed and applied for the synthesis of natural product cephalandole A. Abstract : A novel and efficient iron-catalyzed sp 3 carbon–hydrogen bond functionalization of benzoxazinone derivatives has been developed. For the first time, benzoxazin-2-ones were used as substrates in an oxidative dehydrogenative coupling reaction. The experiments were performed under mild reaction conditions to construct alkyl–aryl C(sp 3 )–C(sp 2 ) bonds. The application of this method to the gram-scale synthesis of natural product cephalandole A has been accomplished in a 3-step sequence. A plausible one electron oxidation involved mechanism is proposed.